2016
DOI: 10.1259/bjr.20160136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intramyocellular and extramyocellular lipids in the paraspinal muscle in patients with chronic low back pain using MR spectroscopy: preliminary results

Abstract: We investigated the detail of the fat content in the paraspinal muscles in patients CLBP and asymptomatic volunteers. The increase of fat content in the Mm of patients with LBP on previous studies was demonstrated to be the increase of IMCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…We previously reported that IMCLs using MRS analysis in the Mm of patients with CLBP was significantly higher than that of asymptomatic volunteers. 26 However, sagittal spinopelvic alignment tended to be different between patients with chronic LBP and asymptomatic volunteers. 27 Therefore, we needed the control group with the same sagittal spinopelvic alignment as the CLBP group to investigate the connection among IMCLs, EMCLs and CLBP.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We previously reported that IMCLs using MRS analysis in the Mm of patients with CLBP was significantly higher than that of asymptomatic volunteers. 26 However, sagittal spinopelvic alignment tended to be different between patients with chronic LBP and asymptomatic volunteers. 27 Therefore, we needed the control group with the same sagittal spinopelvic alignment as the CLBP group to investigate the connection among IMCLs, EMCLs and CLBP.…”
Section: Discussionmentioning
confidence: 96%
“…26 In brief, the Signa HDx 1.5-T MRI system (GE Healthcare, Milwaukee, WI) with a spine coil was used to obtain T 2 weighted sagittal and transverse MR images. From these images, the proton MRS volume of interest (VOI) was positioned in the centre of the Mm at L4/L5 for the right side ( Figure 3).…”
Section: Mri Protocol and Analysis For Mr Spectroscopic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, elevated levels of TAG 50:2 in circulation may represent the early cascade of alterations in cardiovascular risk factors and intramyocellular storage that have been associated with LBP (Goodson et al, 2013; Leino-Arjas et al, 2006; Takashima et al, 2016). To date, we are not aware of any studies that have examined lipid levels in relation to peripheral and central sensitivity, although fat distribution has been shown to influence pressure pain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…It has been posited that the increase in circulating lipids among individuals with LBP contributes to lumbar artherosclerosis, resulting in accelerated degenerative disc disease and higher fat content of the multifidus muscle (Mengiardi et al, 2006). More detailed investigation of the lipid content of the multifidus muscle revealed an increase in intramyocellular lipids in patients with LBP compared to asymptomatic volunteers (Takashima et al, 2016). Although it is currently unclear whether elevated levels of circulating lipids increase vulnerability to developing chronic LBP, both higher BMI and triglyceride levels have been reported in patients with chronic LBP compared to healthy controls (Rinaldo et al, 2016).…”
mentioning
confidence: 99%